DESIGNING NCT APPS FOR 10TH GRADE SENIOR HIGH SCHOOL - Hidayat, Rohmat; Fitri, Hartanti Wahyu Ning; Agustina, Ufa Wulan (Universitas KH. A. Wahab Hasbullah, 2021)
The ability of the teacher to understand and teach technology greatly affects students' abilities in their learning process. By developing technology, it can improve the quality of education in the school. Therefore, the researchers aim to design learning media for students in first grade on senior high school level. This research is designing learning media through an application to learn English Grammar in writing skills at senior high school levels. In this study using Research and Development (R&D) method and through ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. This learning media called as NCT Apps (NCT Application). This learning media is an application designed to develop products in order to test feasibility as an alternative learning media that can help students understand English Grammar in writing skills. The research instrument is a distribute questionnaire on 15 students of the first grade of MA Al-Bairuny Jombang as a sample. The results of this study show that: (1) the results of the media expert score are 3.41. (2) The results of the material expert score are 4 (3) The results of the product test to the students are 4.1. Researchers concluded that Neo Structure Technology Application (NCT Apps) is suitable to use in Grammar learning process in the classroom. From these results, there suggestion that product is revised as suggested from the expert. . Keywords: NCT Application, Language Skills, Structure of Sentences, Hyperlink.